Efficacy of Obturator Nerve Block During Transurethral Resection on Non-muscle invasive Intermediate and High Risk Lateral Wall Bladder Tumours: A Prospective Randomized Controlled Study - Doluoglu, Omer Gokhan; Yildiz, Ali Kaan; Kacan, Turgay; Bayburtluoglu, Veysel; Bektas, Meltem; Ozgur, Berat Cem (Urology Journal, 2022)
Purpose: We aimed to investigate the effects of obturator nerve block (ONB) on obturator reflex, incomplete resection, perforation, progression and recurrence of tumor, presence of muscle tissue in the specimen, need for a second transurethral resection (TURBT) of bladder tumors, and postoperative complications in patients who underwent TURBT for intermediate-high risk lateral wall non-muscle invasive bladder cancers (NMIBC). Material and Methods: Patients were assigned to one of two groups by drawing lots: ONB or none ONB. Early and late recurrence, tumor progression, obturator reflex beat, incomplete resection, perforation, presence of muscle layer in pathology, second TURBT application, operation time, postoperative hospital stay, and complications were compared between the two groups. Results: The median follow-up time of the study was32 (23-41) months. Interquartile range (IQR) was 9. Tumor recurrence at the 3rd month cystoscopy controls was observed in 5 (9.8%) patients in the ONB group, while it was observed in 11 (20.8%) patients in the nONB group (p=0.01). Late tumor recurrence was observed in 10 patients (19.6%) in the ONB group, and in 20 patients (37.7%) in the nONB group (p=0.041). The RFS rate at 12th month was 84% in the ONB group, 69% in the nONB group, 79% in the ONB group at 36th month, and 58% in the nONB group at 36 months, the PFS rate was 94% in the ONB group, while it was 85% in the nONB group (p=0.041). Conclusion: Our study showed that ONB decrease the early and late recurrence and increase recurrence free survival in patients with intermediate-high risk lateral wall bladder cancer.